Magnetic separation process and preparation method of ultra-pure conductive nano carbon material

By adopting multi-stage magnetic separation process and process optimization in the production process of conductive nanocarbon materials, the problems of ferromagnetic substances and impurities in conductive nanocarbon materials are solved, the purity and quality level of the product are improved, and the conductivity and consistency are improved. , and extends the life of the equipment.

CN119240668AInactive Publication Date: 2025-01-03SHANDONG LIANKE NEW MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411452533.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The presence of ferromagnetic substances and impurities in conductive nanocarbon materials affects the purity and quality of the product, resulting in an increase in the residual content of the washing screen, and seriously affects the performance and use requirements of the terminal products.

Method used

The magnetic separation process and preparation method of ultrapure conductive nanocarbon materials are adopted, including raw material selection and pretreatment, process oil coordination, combustion reaction, crushing and collection, wet granulation and drying and multi-stage magnetic separation, through multiple magnetic Selection and process optimization to reduce the content of ferromagnetic substances and impurities.

Benefits of technology

It significantly reduces the content of ferromagnetic substances and impurities, improves the purity and quality level of the product, improves the conductivity and product consistency, extends the equipment life and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005089562540000011
    Figure HDA0005089562540000011
Patent Text Reader

Abstract

The invention provides a magnetic separation process and a preparation method of an ultra-pure conductive nano-carbon material, and aims to reduce the content of ferromagnetic substances and washing screen residues in a product and improve the purity, stability and quality grade of the conductive nano-carbon material. The method comprises the following steps: selecting and pretreating raw materials; passing through a 8000 gauss magnetic separation device to preliminarily remove ferromagnetic substances; in the granulation process, the binder concentration and process parameters are controlled; and after drying, further removing impurities by virtue of a screening machine and multi-stage magnetic separation (including a 10000-gauss automatic magnetic cleaning magnetic separation box and a 6000-gauss drum-type magnetic separator), so as to finally obtain the ultra-pure conductive nano carbon material. According to the method, through a multi-stage magnetic separation process and strict raw material treatment, the content of ferromagnetic substances and washing screen residues in the product is effectively reduced, the purity and the conductivity of the conductive nano carbon material are remarkably improved, the quality requirement of the high-end application field is met, and the important industrial application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and more particularly to a magnetic separation process and a preparation method of ultra-pure conductive nano-carbon materials. Background Art

[0002] In the production process of conductive nano-carbon materials, ferromagnetic substances are inevitably produced. These ferromagnetic substances will seriously affect the quality of conductive nano-carbon materials after being mixed into the products. The ferromagnetic substances contained in conductive nano-carbon materials mainly come from three aspects:

[0003] (1) Ferromagnetic substances contained in the raw materials themselves, such as raw oil, process water, binder, etc.;

[0004] (2) Ferromagnetic substances caused by corrosion of process equipment: Most of the storage equipment and production equipment for conductive nanocarbon materials are made of carbon steel, which will corrode during the production process, causing ferromagnetic substances to enter the carbon black production system. Especially when the production line is under maintenance, the ferromagnetic substances that have not fallen off the equipment will enter the production system. When the production line is restarted, the ferromagnetic substances in the production system will increase significantly.

[0005] (3) Ferromagnetic substances also mainly come from the pipelines that transport conductive nano-carbon materials, including: raw material pipelines, process water pipelines, air pipelines, and gas pipelines. Most of these pipelines are carbon steel pipelines, which will also be corroded after long-term use, causing ferromagnetic substances to fall off and enter the production system along with the raw materials transported through the pipelines.

[0006] These ferromagnetic substances enter the powdered conductive nano-carbon material. After granulation, the ferromagnetic substances are wrapped in the particles and are difficult to remove, which further increases the content of the product's water washing residue and does not meet the production and use requirements of the terminal product.

[0007] In addition, conductive nano-carbon materials will also produce impurities such as hard carbon and coke particles during production, which seriously affect the purity of the product, are not conducive to the extrusion and dispersion performance of downstream products, and easily lead to current breakdown and other phenomena in the terminal products. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a magnetic separation process route for conductive nano-carbon materials and a new preparation method thereof, which reduces the ferromagnetic substances in the nano-conductive carbon materials, reduces the water washing residues, and improves the purity, stability and quality grade of the products.

[0009] To achieve the above object, the present invention provides the following technical solutions, which mainly include:

[0010] A magnetic separation process and preparation method of ultra-pure conductive nano-carbon material, comprising the following steps:

[0011] (1) Raw material selection and pretreatment:

[0012] The feedstock oil with low toluene insoluble matter and ash content is preferred, and the toluene insoluble matter index meets the following requirements: coal tar ≤6%, ethylene tar ≤0.8%, anthracene oil ≤0.8%, carbon black oil ≤5.5%; the ash content index meets the following requirements: coal tar ≤0.11%, ethylene tar ≤0.05%, anthracene oil ≤0.05%, carbon black oil ≤0.1%;

[0013] The crude oil is placed in a static state for 48 hours, the temperature is controlled at 50-55°C, and then the water and impurities are removed by centrifugal separation and multi-stage filtration (the filter mesh is 100 mesh), and dehydrated to a water content of ≤1.0%;

[0014] The process water is treated by multi-media filtration, activated carbon filtration, precision filtration, reverse osmosis, mixed bed and deoxygenation to obtain pure process water for production;

[0015] The binder for granulation is pure liquid sodium lignin sulfonate with water insoluble matter ≤ 0.2%, ash content ≤ 5%, and 325 mesh water washing residue ≤ 3%;

[0016] (2) Process oil formulation:

[0017] According to the process requirements, the selected raw material oil is mixed in the following proportions: anthracene oil 70-80%, ethylene tar 20-30%, or coal tar 10-15%, carbon black oil 5-10%, ensuring that the process oil meets the moisture ≤ 0.8%, density 1.05-1.13g / cm 3 , ash content ≤ 0.05%, viscosity at 80℃ ≤ 5.5, asphaltene ≤ 5%;

[0018] (3) Combustion reaction:

[0019] Use high calorific value natural gas as fuel, and control the flow rate at 730±20Nm 3 / h, and completely burn with 900-920℃ preheated air in the reactor to produce a high-temperature combustion airflow of about 2000℃;

[0020] Insert 8 process oil guns with a spray angle of 30° in the throat section. Preheat the process oil to 200-210°C with a flow rate of 5500-6500kg / h to react with the high-temperature combustion airflow;

[0021] Insert four quenching water guns radially in the quenching section, spray 3500±500kg / h of process water axially, and the quenching pressure is 1.5±0.3MPa to terminate the reaction;

[0022] (4) Crushing and collection:

[0023] The flue gas containing the conductive nano-carbon material generated by the reaction enters the main bag filter, and the powdered conductive nano-carbon material is separated and processed by a micron grinder and a classifier, and then collected into a powdered conductive nano-carbon material storage tank;

[0024] (5) Wet granulation:

[0025] Before entering the granulator, the powdered conductive nanocarbon material is initially magnetically separated by an automatic magnetic separation box with a magnetic field strength of 8000GS;

[0026] Granulation water and binder are mixed at a flow rate ratio of 25-35, the binder concentration is 50±5kg / can, and the granulator frequency is set at 55%-60% for wet granulation;

[0027] (6) Drying and multi-stage magnetic separation:

[0028] The wet material after granulation enters the dryer for drying. The dried particles are screened by the screening machine, and the qualified particles are magnetically separated again by the automatic magnetic separation box with a magnetic field strength of 10000GS.

[0029] The particles are lifted to the air separator by the finished product conveying auger. The air-separated particles enter the drum magnetic separator with a magnetic field strength of 6000GS to remove larger ferromagnetic substances.

[0030] Before entering the finished product can and packaging machine, a manual magnetic cleaning device and an automatic magnetic cleaning magnetic separation box with a magnetic field strength of 10,000 GS are set up respectively, and finally ultra-pure conductive nano-carbon materials are obtained;

[0031] Preferably, the feedstock oil is selected from one or more of the following oils: coal tar B, ethylene tar B, anthracene oil B, and carbon black oil A.

[0032] Preferably, the process oil is mixed in the following proportions: anthracene oil B 70%, ethylene tar B 30%; or coal tar B 10%, anthracene oil B 80%, ethylene tar B 10%; or carbon black oil A 5%, anthracene oil B 80%, ethylene tar B 15%.

[0033] Preferably, the process oil preheating temperature is 200-210°C, the process oil gun nozzle spray angle is 30°, and the process oil flow rate is 5500-6500 kg / h.

[0034] Preferably, the quenching process water is process water after multi-stage treatment, the quenching pressure is controlled at 1.5±0.3MPa, and the quenching water flow rate is 3500±500kg / h.

[0035] Preferably, the magnetic field strength of the magnetic separation device is: 8000GS, 10000GS, 6000GS, and 10000GS respectively.

[0036] Preferably, the conductive nano-carbon material has a water-wash residue content of ≤3ppm, a toluene extract transmittance of ≥99%, a volume resistivity of 4.8-5.4Ω·cm at 20°C, and contains no ferromagnetic substances.

[0037] The invention discloses an ultra-pure conductive nano-carbon material prepared by a preparation method.

[0038] Preferably, it is suitable for the production field of high-performance conductive materials, improves the extrusion performance, dispersion performance and conductivity of downstream products, and reduces the occurrence of quality problems such as current breakdown.

[0039] It can be seen from the above technical solution that compared with the existing technology, by systematically optimizing the production process, from raw material selection, pretreatment to process control and multi-stage magnetic separation, the purity and quality level of the product are significantly improved. The specific beneficial effects are as follows:

[0040] 1. Reduce the content of ferromagnetic substances and improve product purity:

[0041] Source control: Select raw oil with low toluene insoluble matter and ash content, and use pure liquid sodium lignin sulfonate as a binder to reduce the introduction of ferromagnetic substances and impurities at the raw material level.

[0042] Raw material pretreatment: The crude oil is refined by static sedimentation, centrifugal separation and multi-stage filtration to effectively remove impurities such as moisture, asphaltene and residue.

[0043] Process water purification: The process water is treated with multi-stage filtration and deoxygenation to avoid the corrosion of impurities and oxygen in the water to the system and reduce the generation of ferromagnetic substances.

[0044] 2. Multi-stage magnetic separation process to completely remove ferromagnetic impurities:

[0045] Before the powdered conductive nano-carbon material enters the granulator, and in key links such as drying, screening, air separation and packaging, high magnetic field strength magnetic separation devices (8000GS, 10000GS, 6000GS) are set up multiple times to achieve the step-by-step removal of ferromagnetic substances.

[0046] Optimized configuration of magnetic separation device: Through the combination of automatic and manual magnetic separation devices, the magnetic separation process is ensured to be efficient and continuous, minimizing the content of ferromagnetic impurities in the product.

[0047] 3. Reduce the content of water-washed residue and improve product quality stability:

[0048] Crushing and grading treatment: Add a classifier after the micron crusher to further refine the particle size and reduce the presence of impurities such as hard carbon and coke particles.

[0049] Optimize combustion reaction conditions: Accurately control the fuel, air preheating temperature, process oil preheating temperature and flow rate, reduce the formation of hard carbon and coke particles, and reduce the content of water washing residue.

[0050] Test results: The water washing residue content of the product is reduced to 2-3ppm, which is significantly better than the existing technical level.

[0051] 4. Improve electrical conductivity and product consistency:

[0052] Performance improvement brought by high purity: Pure conductive nanocarbon materials have better conductive network structure, and the volume resistivity at 20°C is stable between 4.8-5.4Ω·cm, meeting the requirements of high-performance conductive materials.

[0053] Enhanced product consistency: Strict process control and quality testing ensure consistency between product batches, improving reliability in downstream applications.

[0054] 5. Extend equipment life and reduce production costs:

[0055] Anti-corrosion measures: Deoxygenation treatment of process water and refining of crude oil reduce oxygen corrosion of system pipelines and equipment, extend the service life of equipment and reduce maintenance costs.

[0056] Economical: Under the premise of ensuring product quality, the rational use of carbon steel pipes and equipment avoids the high cost of using all stainless steel materials and improves the economic benefits of production. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0058] Figure 1 It is a schematic diagram of the process of the present invention.

[0059] Figure 2 It is a schematic diagram of the reaction furnace of the present invention. DETAILED DESCRIPTION

[0060] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example

[0062] The present invention provides a magnetic separation process and preparation method for ultra-pure conductive nano-carbon materials, aiming to reduce the content of ferromagnetic substances and water washing residues in the product and improve the purity, stability and quality grade of the conductive nano-carbon materials. The method comprises the following steps:

[0063] Raw material selection and pre-treatment: Select raw oils with low toluene insolubles and ash content (coal tar, ethylene tar, anthracene oil, carbon black oil) for process oil preparation; use pure liquid sodium lignin sulfonate as a binder for granulation. The raw oil is subjected to static sedimentation, centrifugal separation and multi-stage filtration to remove moisture and impurities; the process water is subjected to multi-media filtration, activated carbon filtration, precision filtration, reverse osmosis, mixed bed and deoxygenation treatment to obtain high-purity production water.

[0064] Process oil preparation: According to the process requirements, anthracene oil, ethylene tar, coal tar and carbon black oil are mixed in a certain proportion to ensure that the moisture, density, ash content, viscosity and asphaltene indicators of the process oil meet the standards.

[0065] Combustion reaction: Use high calorific value natural gas and preheated air to completely burn in the reactor to generate high-temperature combustion airflow; after preheating, the process oil is sprayed into the throat section through a nozzle at a specific angle and flow rate to react with the high-temperature airflow to generate conductive nano-carbon materials; the quenching section uses treated process water for rapid cooling to terminate the reaction.

[0066] Crushing and collection: The carbon-containing flue gas generated by the reaction is separated into powdered conductive nano-carbon materials through the main bag filter, processed by a micron crusher and a classifier, and collected in a storage tank.

[0067] Wet granulation and multi-stage magnetic separation: Before entering the granulator, the powdered material passes through an 8000 Gauss magnetic separation device to initially remove ferromagnetic substances; during the granulation process, the binder concentration and process parameters are controlled; after drying, impurities are further removed through a screening machine and multi-stage magnetic separation (including a 10,000 Gauss automatic magnetic separation box and a 6000 Gauss drum magnetic separator), ultimately obtaining ultra-pure conductive nano-carbon materials.

[0068] The specific steps are as follows:

[0069] (1) Raw material selection

[0070] Optimization of raw oil:

[0071] Select the origin of raw oil, and select oils with toluene insolubles and low ash content for process oil blending. The toluene insoluble content index must meet the following requirements: coal tar ≤6%, ethylene tar ≤0.8%, anthracene oil ≤0.8%, carbon black oil ≤5.5%; the ash content index must meet the following requirements: coal tar ≤0.11%, ethylene tar ≤0.05%, anthracene oil ≤0.05%, carbon black oil ≤0.1%. Eight oils, including coal tar A, coal tar B, ethylene tar A, ethylene tar B, anthracene oil A, anthracene oil B, carbon black oil A, and carbon black oil B, were selected from the main raw material suppliers for testing experiments. The test results are as follows:

[0072]

[0073] From the test results in the above table, we selected coal tar B, ethylene tar B, anthracene oil B, and carbon black oil A with relatively low toluene insolubles and ash content as spare oils. The ferromagnetic substances therein can be removed or reduced by the raw material pretreatment, process oil preparation, and magnetic separation assistance of the present invention.

[0074] Preferred binders:

[0075] Pure liquid sodium lignin sulfonate is preferably used as a binder for granulation, and the water-insoluble matter must be ≤0.2%, the ash content must be ≤5%, and the 325-mesh water-washed sieve residue must be ≤3%.

[0076] (2) Crude oil classification and storage

[0077] According to the test indicators, the crude oil is unloaded into the designated storage tanks to implement classified storage of crude oil to prevent mixed storage that affects the quality of crude oil. Three 3000m 3 There are 8 crude oil storage tanks, including No. 1 and No. 2 for carbon black oil, No. 3 and No. 4 for coal tar, No. 5 and No. 6 for anthracene oil, and No. 7 and No. 8 for ethylene tar. Mixing of tanks is strictly prohibited. When unloading the oil, filter it with a 20-mesh screen, then enter the oil unloading pool, and transport it to the corresponding oil storage tank through the oil unloading pump.

[0078] (3) Raw material pretreatment

[0079] Crude oil refining treatment:

[0080] The crude oil in the oil storage tank is left to stand for more than 48 hours, so that the water and impurities in the crude oil are initially separated by natural sedimentation under the action of gravity, and the standing temperature is controlled between 50-55°C. Then, the water and part of the asphaltene and residue in the crude oil are separated from the oil by centrifugal separation. The temperature of the oil storage tank is gradually raised to 60°C-95°C, and further dehydration treatment is carried out to control the water content of the crude oil to be below 1.0%. The crude oil in the oil tank is subjected to 24-hour uninterrupted circulation multi-stage filtration treatment by using a circulating pump, and the filter mesh number is 100 mesh to filter out the remaining residues and other impurities in the crude oil.

[0081] Process water treatment:

[0082] The raw water is filtered through a multi-media filter to remove colloids and some microorganisms in the water, and the activated carbon filter is used to remove impurities such as COD, microorganisms, and residual chlorine in the water. The impurities above 5μm in the water are filtered out through a precision filter, and the water is desalted through a first-level reverse osmosis device. Then, the anions and cations in the water are eliminated through a mixed bed to increase the water resistivity and obtain desalted water. The desalted water at 104℃ is pumped into the deaerator through a desalting water pump to remove free oxygen to protect the system pipelines and equipment from oxygen corrosion, and finally the process water for production is obtained.

[0083] flow chart:

[0084] Raw water pump → multi-media filter → activated carbon filter → precision filter → primary reverse osmosis → intermediate water tank → mixed bed → desalted water pump → heat pipe heat exchanger → deaerator → process water for production

[0085] (4) Process oil formulation

[0086] The process oil must meet the requirements of moisture content ≤ 0.8%, density between 1.05-1.13g / cm3, ash content ≤ 0.05%, viscosity at 80℃ ≤ 5.5, and asphaltene ≤ 5%. According to the above (1) raw material selection and the method of fixed process parameter test, the process oil mixing ratio is determined as follows: anthracene oil B 70%, ethylene tar B 30% or coal tar B10%, anthracene oil B 80%, ethylene tar B10%, or carbon black oil A 5%, anthracene oil B 80%, ethylene tar 15%.

[0087] (5) Combustion reaction

[0088] The fuel uses pure high calorific value natural gas, and the flow rate is controlled at 730±20Nm 3 / h, mixed with 900℃-920℃ preheated air through a burner and completely burned in the conductive nano-carbon material reactor, generating a 2000℃ high-temperature combustion airflow that enters the reactor throat section.

[0089] In the throat section, the process oil reacts with the high-temperature and high-speed combustion airflow from the burner. 8 process oil guns are inserted into the throat section, and the nozzle of the process oil gun has a spray angle of 30°. The process oil is first preheated to 200-210°C by a preheater to reduce the viscosity and surface tension, which is beneficial to improve the degree of atomization, shorten the reaction time, and reduce the formation of hard carbon during the reaction. The process oil flow rate is controlled to be 5500-6500kg / h to ensure the atomization effect of the process oil when it is sprayed out, prevent coking, and form coke particles. In the termination reaction quenching section, 4 quenching water guns are inserted radially, and 3500±500kg / h of treated process water is sprayed axially. The termination quenching pressure is controlled at 1.5±0.3MPa to ensure the atomization effect of the quenching water gun. The quenching process water is evenly sprayed into the flue gas of the conductive nano-carbon material to terminate the reaction. The flue gas containing powder enters the main bag filter through the pipeline.

[0090] (6) Collection

[0091] The flue gas of the conductive nano-carbon material is separated in the main bag filter, and the separated powdered conductive nano-carbon material enters the air delivery pipeline. The residue in the conductive nano-carbon material is initially crushed by a micron grinder, and then ground by a classifier and transported to the collection bag filter. The collected conductive nano-carbon material enters the powdered conductive nano-carbon material storage tank.

[0092] (7) Wet granulation

[0093] The powdered conductive nano-carbon material enters the granulator through the feeding pump. Before entering the granulator, an 8000GS automatic magnetic separation box is added to preliminarily separate the powdered conductive nano-carbon material and ferromagnetic substances.

[0094] The granulation water required for granulation is sent from the process water tank to the static mixer through the process water pump, and the binder pure liquid sodium lignin sulfonate used for granulation is sent from the binder tank to the static mixer through the binder pump. The mixed granulation liquid enters the wet granulator for granulation. The concentration of the binder pure liquid sodium lignin sulfonate is controlled at 50±5kg / tank, the granulator frequency is set at 55%-60%, and the flow ratio of granulation process water to binder is controlled between 25-35.

[0095] (8) Drying

[0096] The wet conductive nano-carbon material particles granulated by the granulator enter the dryer for drying. The drying heat required by the dryer is supplied by the tail gas combustion furnace, and the tail gas combustion furnace is supplied with air by the tail gas furnace fan. Together with the tail gas sent by the tail gas pressure fan, it enters the tail gas combustion furnace for low-nitrogen combustion. The high-temperature gas generated by the combustion enters the fire box of the dryer for indirect drying.

[0097] (9) Multi-stage magnetic separation

[0098] The dried conductive nano-carbon material enters the screening machine through the elevator for screening. The qualified particles are again passed through the automatic magnetic cleaning magnetic separation box with a magnetic field strength of 10000GS. The magnetically selected particles pass through the finished product conveying auger and are lifted to the air separator for the second time. The air-selected particles enter the drum magnetic separator with a magnetic field strength of 6000GS to remove larger ferromagnetic substances. Before entering the finished product tank, a manual magnetic cleaning device is set up for manual regular magnetic cleaning. Before entering the packaging machine, a 10000GS automatic magnetic cleaning magnetic separation box is added. After the conductive nano-carbon material after magnetic selection is sampled and tested, it is packaged and put into storage.

[0100] (1) Select the origin of the raw oil, and preferably use oils with toluene insolubles and low ash content for process oil blending. The toluene insoluble content index must meet the following requirements: coal tar ≤6%, ethylene tar ≤0.8%, anthracene oil ≤0.8%, and carbon black oil ≤5.5%; the ash content index must meet the following requirements: coal tar ≤0.11%, ethylene tar ≤0.05%, anthracene oil ≤0.05%, and carbon black oil ≤0.1%.

[0101] Pure liquid sodium lignin sulfonate is preferably used as a binder for granulation, and the water-insoluble matter must be ≤0.2%, the ash content must be ≤5%, and the 325-mesh water-washed sieve residue must be ≤3%.

[0102] (2) Raw material pretreatment

[0103] Crude oil refining treatment:

[0104] The crude oil in the oil storage tank is left to stand for more than 48 hours, so that the water and impurities in the crude oil are initially separated by natural sedimentation under the action of gravity, and the standing temperature is controlled between 50-55°C. Then, the water and part of the asphaltene and residue in the crude oil are separated from the oil by centrifugal separation. The temperature of the oil storage tank is gradually raised to 60°C-95°C, and further dehydration treatment is carried out to control the water content of the crude oil to be below 1.0%. The crude oil in the oil tank is subjected to 24-hour uninterrupted circulation multi-stage filtration treatment by using a circulating pump, and the filter mesh number is 100 mesh to filter out the remaining residues and other impurities in the crude oil.

[0105] Process water treatment:

[0106] The raw water is filtered through a multi-media filter to remove colloids and some microorganisms in the water, and the activated carbon filter is used to remove impurities such as COD, microorganisms, and residual chlorine in the water. The impurities above 5μm in the water are filtered out through a precision filter, and the water is desalted through a first-level reverse osmosis device. Then, the anions and cations in the water are eliminated through a mixed bed to increase the water resistivity and obtain desalted water. The desalted water at 104℃ is pumped into the deaerator through a desalting water pump to remove free oxygen, improve the purity of the water quality, and protect the system pipelines and equipment from oxygen corrosion, and finally obtain process water for production.

[0107] (3) Process oil formulation

[0108] The process oil must meet the requirements of moisture content ≤ 0.8%, density between 1.05-1.13g / cm3, ash content ≤ 0.05%, viscosity at 80℃ ≤ 5.5, and asphaltene ≤ 5%. According to the above (1) raw material selection and the method of fixed process parameter test, the process oil mixing ratio is determined as follows: anthracene oil B 70%, ethylene tar B 30% or coal tar B10%, anthracene oil B 80%, ethylene tar B10%, or carbon black oil A 5%, anthracene oil B 80%, ethylene tar 15%.

[0109] (4) Combustion reaction

[0110] The fuel uses pure high calorific value natural gas, and the flow rate is controlled at 730±20Nm 3 / h, mixed with 900℃-920℃ preheated air through a burner and completely burned in the conductive nano-carbon material reactor, generating a 2000℃ high-temperature combustion airflow that enters the reactor throat section.

[0111] In the throat section, the process oil reacts with the high-temperature and high-speed combustion airflow from the burner. Eight process oil guns are inserted into the throat section, and the nozzle of the process oil gun has a spray angle of 30°. The process oil is first preheated to 200-210°C by a preheater to reduce the viscosity, and the process oil flow is controlled to be 5500-6500kg / h to ensure the atomization effect of the process oil when it is sprayed out to prevent coking and the formation of coke particles. In the termination reaction quenching section, four quenching water guns are inserted radially, and 3500±500kg / h of treated process water is sprayed axially. The termination quenching pressure is controlled at 1.5±0.3MPa to ensure the atomization effect of the quenching water gun, and the quenching process water is evenly sprayed into the flue gas of the conductive nano-carbon material.

[0112] (5) Collection

[0113] A classifier is added at the rear of the micron grinder for collection.

[0114] (6) Wet granulation

[0115] The powdered conductive nano-carbon material enters the granulator through the feeding pump. Before entering the granulator, an 8000GS automatic magnetic separation box is added to preliminarily separate the powdered conductive nano-carbon material and ferromagnetic substances.

[0116] The granulation water required for granulation is sent from the process water tank to the static mixer through the process water pump, and the binder pure liquid sodium lignin sulfonate used for granulation is sent from the binder tank to the static mixer through the binder pump. The mixed granulation liquid enters the wet granulator for granulation. The concentration of the binder pure liquid sodium lignin sulfonate is controlled at 50±5kg / tank, the granulator frequency is set at 55%-60%, and the flow ratio of granulation process water to binder is controlled between 25-35.

[0117] (7) Multi-stage magnetic separation

[0118] The dried conductive nano-carbon material enters the screening machine through the elevator for screening. The qualified particles are again passed through the automatic magnetic cleaning magnetic separation box with a magnetic field strength of 10000GS. The magnetically selected particles pass through the finished product conveying auger and are lifted to the air separator for the second time. The air-selected particles enter the drum magnetic separator with a magnetic field strength of 6000GS to remove larger ferromagnetic substances. Before entering the finished product tank, a manual magnetic cleaning device is set up for manual regular magnetic cleaning. Before entering the packaging machine, a 10000GS automatic magnetic cleaning magnetic separation box is added. After the conductive nano-carbon material after magnetic selection is sampled and tested, it is packaged and put into storage.

[0119] The present invention seeks solutions from several aspects, including raw materials, combustion reaction, and process magnetic separation assistance, thereby reducing the content of ferromagnetic substances from the root, reducing water washing residues, and improving product purity.

[0120]

[0121] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0122] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A magnetic separation process and preparation method of ultra-pure conductive nano-carbon material, characterized in that: The following steps are involved: (1) Raw material selection and pretreatment: The feedstock oil with low toluene insoluble matter and ash content is preferred, and the toluene insoluble matter index meets the following requirements: coal tar ≤6%, ethylene tar ≤0.8%, anthracene oil ≤0.8%, carbon black oil ≤5.5%; the ash content index meets the following requirements: coal tar ≤0.11%, ethylene tar ≤0.05%, anthracene oil ≤0.05%, carbon black oil ≤0.1%; The crude oil is placed in a static state for 48 hours, the temperature is controlled at 50-55°C, and then the water and impurities are removed by centrifugal separation and multi-stage filtration (the filter mesh is 100 mesh), and dehydrated to a water content of ≤1.0%; The process water is treated by multi-media filtration, activated carbon filtration, precision filtration, reverse osmosis, mixed bed and deoxygenation to obtain pure process water for production; The binder for granulation is pure liquid sodium lignin sulfonate with water insoluble matter ≤ 0.2%, ash content ≤ 5%, and 325 mesh water washing residue ≤ 3%; (2) Process oil formulation: According to the process requirements, the selected raw material oil is mixed in the following proportions: anthracene oil 70-80%, ethylene tar 20-30%, or coal tar 10-15%, carbon black oil 5-10%, ensuring that the process oil meets the moisture ≤ 0.8%, density 1.05-1.13g / cm 3 , ash content ≤ 0.05%, viscosity at 80℃ ≤ 5.5, asphaltene ≤ 5%; (3) Combustion reaction: Use high calorific value natural gas as fuel, and control the flow rate at 730±20Nm 3 / h, and completely burn with 900-920℃ preheated air in the reactor to produce a high-temperature combustion airflow of about 2000℃; Insert 8 process oil guns with a spray angle of 30° in the throat section. Preheat the process oil to 200-210°C with a flow rate of 5500-6500kg / h to react with the high-temperature combustion airflow; Insert four quenching water guns radially in the quenching section, spray 3500±500kg / h of process water axially, and the quenching pressure is 1.5±0.3MPa to terminate the reaction; (4) Crushing and collection: The flue gas containing the conductive nano-carbon material generated by the reaction enters the main bag filter, and the powdered conductive nano-carbon material is separated and processed by a micron grinder and a classifier, and then collected into a powdered conductive nano-carbon material storage tank; (5) Wet granulation: Before entering the granulator, the powdered conductive nanocarbon material is initially magnetically separated by an automatic magnetic separation box with a magnetic field strength of 8000GS; Granulation water and binder are mixed at a flow rate ratio of 25-35, the binder concentration is 50±5kg / can, and the granulator frequency is set at 55%-60% for wet granulation; (6) Drying and multi-stage magnetic separation: The wet material after granulation enters the dryer for drying. The dried particles are screened by the screening machine, and the qualified particles are magnetically separated again by the automatic magnetic separation box with a magnetic field strength of 10000GS. The particles are lifted to the air separator by the finished product conveying auger. The air-separated particles enter the drum magnetic separator with a magnetic field strength of 6000GS to remove larger ferromagnetic substances. Before entering the finished product cans and packaging machines, a manual magnetic cleaning device and an automatic magnetic cleaning magnetic separation box with a magnetic field strength of 10,000 GS are set up respectively, and finally ultra-pure conductive nano-carbon materials are obtained.

2. The preparation method according to claim 1, characterized in that: The raw material oil is selected from one or more of the following oil products: coal tar B, ethylene tar B, anthracene oil B, and carbon black oil A.

3. The preparation method according to claim 1, characterized in that: The process oil is mixed in the following proportions: anthracene oil B 70%, ethylene tar B 30%; or coal tar B 10%, anthracene oil B 80%, ethylene tar B 10%; or carbon black oil A 5%, anthracene oil B 80%, ethylene tar B 15%.

4. The preparation method according to claim 1, characterized in that: The process oil preheating temperature is 200-210°C, the process oil gun nozzle spray angle is 30°, and the process oil flow rate is 5500-6500kg / h.

5. The preparation method according to claim 1, characterized in that: The quenching process water is process water that has undergone multi-stage treatment, the quenching pressure is controlled at 1.5±0.3MPa, and the quenching water flow rate is 3500±500kg / h.

6. The preparation method according to claim 1, characterized in that: The magnetic field strengths of the magnetic separation device are: 8000GS, 10000GS, 6000GS, and 10000GS respectively.

7. The preparation method according to claim 1, characterized in that: The conductive nano-carbon material has a water-wash residue content of ≤3ppm, a toluene extract transmittance of ≥99%, a volume resistivity of 4.8-5.4Ω·cm at 20°C, and contains no ferromagnetic substances.

8. An ultra-pure conductive nano-carbon material prepared by the preparation method according to any one of claims 1 to 7.

9. The ultra-pure conductive nano-carbon material according to claim 8, characterized in that: It is suitable for the production of high-performance conductive materials, improves the extrusion performance, dispersion performance and conductivity of downstream products, and reduces the occurrence of quality problems such as current breakdown.

Citation Information

Patent Citations

  • Method for producing conductive carbon black for cable jackets

    CN102796403A

  • Method for producing carbon black for shielding material inside cable

    CN109054459A

  • Production method for high-purity carbon black

    CN109321005A

  • Production method of conductive carbon black for environment-friendly cable shielding material

    CN112322077A

  • Technology for removing ferromagnetic substances in carbon black

    CN112973962A